Pudendal Nerve Injuries in Sports and Exercise: A Case Series of Pudendal Neuropathies From Squats. Issue 1 (January 2021) - Kasitinon, Donald; Kelly, Brian; Price, Taylor L.; Chhabra, Avneesh; Scott, Kelly M.
Abstract : Background: Pudendal neuropathy is an underrecognized cause of pelvic pain that can be difficult to diagnose and treat. Cycling has been the traditional etiology associated with exercise-induced pudendal neuropathy, but with changing aesthetic and societal norms emphasizing a strong physique, there has been increasing anecdotal evidence of squat-based exercises causing the condition. Study Design: Case series. A retrospective medical record review was performed to look at all patients with pudendal nerve injuries who presented to a physical medicine and rehabilitation pelvic floor rehabilitation clinic over a 1-year period. Case Description: There were 15 cases of pudendal neuropathy thought to be due to squat-based exercises. Here, we present 4 of these patients (1 male and 3 females) who had good follow-up and compliance with treatment recommendations, along with their respective outcomes. Outcomes: This is the first case series to present a number of patients with pelvic pain due to pudendal neuropathies presumably derived from squat-related exercise. All 4 of these patients had good outcomes utilizing a multidisciplinary approach to management. Discussion: It is important for both physicians and physical therapists to learn to recognize pudendal neuropathy as a cause of pelvic pain and to counsel patients effectively to help them avoid pudendal nerve injury during exercise.